Variation of the auditory system in the Indian Gerbil, Tatera indica Hardwicke, 1807, (Muridae, Rodentia) from the east of Iran - Asghar Khajeh; Zeinolabedin Mohammadi; Fatemeh Ghorbani; Javad Meshkani (Journal of Asia-Pacific Biodiversity, 2019)
The Indian Gerbil (Tatera indica) is one of the most successful species in the east of Iran regarding the population size and distributional range. Many factors are effective in the success of this species, but the tympanic bulla and external ear with a special role in increasing sensitivity could be very important. In this study, these two characters were examined in 108 skulls of the adult Indian Gerbil from different localities in the east of Iran. The results of this study show an increasing trend in the volume of tympanic bulla and length of external ear from higher to the lower latitudes in accordance with Allen's rule. This increase is significant in the southeast Iran population. The increase of the body size in the Indian Gerbil was also documented from the northeast toward the southeast Iran. The negative correlation between the body size and latitude implies thermoregulatory response of the Indian Gerbil to the cold climate of the northeast Iran. It can also reflect food scarcity in desert areas of the southeast Iran comparing with the northeast areas inhabiting by the Indian Gerbil. This study proposed that an increase in auditory sensitivity would be advantageous for the gerbil's ability to escape predation, to mate, and to compete for resources. Keywords: Auditory system, Ear length, Indian Gerbil, Tatera indica, Tympanic bulla